On the clandestine teaching in Lithuania - Žukauskas , K. (Psichologija, 1972)
In the presented article the clandestine teaching and the activity of clandestine schools in Lithuania at the end of the l9th and the beginning of the 20th century are analysed. The practice of clandestine teaching sprang up in Lithuania because of the tsarist policy of national oppression, which abolished the teaching of the mother-tongue in the national school and banned Lithuanian publications. Fighting against the national oppression the Lithuanian people organized the surreptitious teaching of children which was taking place almost in every village. The children were taught by the so-called “daraktoriai”. The tsarist government persecuted and prohibited the clandestine teaching of children, which, despite these prohibitions, was carried on successfully and became a very important factor in strengthening love of one’s country and language, in increasing literacy and raising the culture of the people.